Boron nitride material and application product thereof
By forming a C-axis structure with a thickness of more than 5 nm on hexagonal boron nitride and attaching a polymer with a low solubility parameter, the problem of deterioration of the dielectric loss tangent of boron nitride materials under high humidity is solved, and the hygroscopicity and hygroscopicity are reduced. Effect of dielectric loss tangent.
Patent Information
- Application Number
- CN202380046151.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-23
- Filing Date
- 2023-06-05
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to reduce the dielectric loss tangent of boron nitride materials under high humidity, resulting in deterioration of its hygroscopicity and dielectric loss tangent.
Surface modification is achieved by forming a thickness of more than 5nm in the C-axis direction of hexagonal boron nitride and attaching a polymer with a low solubility parameter, which is lower than 47.9MPa0.5 as determined by methanol titration.
It effectively reduces the dielectric loss tangent of boron nitride materials under high humidity and reduces its hygroscopicity, thus improving the performance of the material.
Smart Images

Figure CN119343315A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to boron nitride materials and application products thereof. Background Art
[0002] In recent years, the application of the fifth-generation mobile communication system (5G) in the field of electronics has expanded, and the performance level required of electronic devices has increased. For example, in order to make the communication speed faster than previous generations, 5G uses a higher frequency band. Therefore, wiring boards that support high frequencies are required in electronic devices.
[0003] The transmission loss in the transmission path of the wiring board depends on the frequency. The higher the signal frequency, the greater the transmission loss. In addition, the transmission loss depends on the dielectric constant and the dielectric loss tangent. Therefore, in order to reduce the transmission loss of high-frequency signals, the substrate material constituting the insulating layer of the wiring board is required to have a low dielectric constant and a low dielectric loss tangent. In particular, in the high-frequency band, the dielectric loss tangent is greatly dependent on the orientation polarization of the organic molecules contained in the substrate material. Therefore, it is required to reduce the polar groups such as hydroxyl and amino groups contained in the substrate material.
[0004] In addition, for large-capacity communications such as 5G, the transmission distance of radio waves is short due to the use of high-frequency bands. Therefore, it is necessary to increase the output power of electronic equipment. In addition, with the realization of high integration and miniaturization, the installation density of circuits is also improved. If you want to meet these necessities, the heat generation per unit area of the wiring board increases. Therefore, the wiring board is required to have high heat dissipation. In order to improve the heat dissipation of the wiring board, a filler with excellent thermal conductivity is contained in the substrate material constituting the insulating layer of the wiring board, thereby improving the thermal conductivity of the wiring board.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5530318
[0008] Non-patent literature
[0009] Non-patent document 1: HS Lee, MW Delatore, M. Miller, PB Messersmith, Science, 2007, 318, 426-430
[0010] Non-patent document 2: Heng Shen, Jing Guo, Hao Wang, Ning Zhao, Jian Xu, ACS Appl. Mater. Interfaces, 2015, 7, 5701-5708
[0011] Non-patent document 3: Yi-Tao Liu, Xu-Ming Xie and Xiong-Ying Ye, Chem. Commun., 2013, 49, 388-390 Summary of the invention
[0012] Problems to be solved by the invention
[0013] As far as the prior art is concerned, it is desirable to reduce the dielectric loss tangent of boron nitride materials under high humidity.
[0014] Means for solving problems
[0015] The present invention provides a boron nitride material, which comprises: hexagonal boron nitride with a thickness of 5 nm or more in the C-axis direction, and a polymer attached to the hexagonal boron nitride, wherein the solubility parameter of the boron nitride material measured by a methanol titration method is lower than 47.9 MPa. 0.5 .
[0016] Effects of the Invention
[0017] According to the present disclosure, the dielectric loss tangent of a boron nitride material under high humidity can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a diagram showing a schematic structure of a boron nitride material in the first embodiment.
[0019] Figure 2 Graph showing the relationship between the HSP distance between a polymer and water and the dielectric loss tangent of a boron nitride material when wet.
[0020] Figure 3 This is a diagram showing a schematic configuration of a resin composition in a fourth embodiment.
[0021] Figure 4 This is a cross-sectional view of a film with resin in the sixth embodiment.
[0022] Figure 5 This is a cross-sectional view of the metal foil with resin in the seventh embodiment.
[0023] Figure 6 It is a cross-sectional view of a metal-clad laminate in the eighth embodiment.
[0024] Figure 7 This is a cross-sectional view of a wiring board in Embodiment 9. DETAILED DESCRIPTION
[0025] (Insights that form the basis of this disclosure)
[0026] Boron nitride is a material with high thermal conductivity and excellent electrical insulation. In particular, boron nitride with a hexagonal crystal structure has a layered structure like graphite, can be synthesized relatively easily, and has excellent characteristics such as thermal conductivity, electrical insulation, chemical stability, and heat resistance. Therefore, boron nitride is expected to be used as a filler for resin compositions used in heat dissipation sheets, thermally conductive insulating substrates, etc.
[0027] However, boron nitride has a hydrophilic surface and absorbs moisture at high humidity. Therefore, when boron nitride is used as a filler, the amount of water contained in the insulating substrate increases, and there is a concern that the dielectric loss tangent may deteriorate. Since the C surface of scaly hexagonal boron nitride occupies most of its surface area, surface modification of the C surface to make the C surface hydrophobic is particularly effective in suppressing water adsorption and reducing the dielectric loss tangent.
[0028] However, the amount of functional groups present on the C-face of the boron nitride particles is extremely small compared to other faces. That is, the C-face of boron nitride is chemically inactive. Therefore, it is difficult to form a direct covalent bond between a known surface modifier such as a silane coupling agent and the C-face of boron nitride and to inhibit the adsorption of water on the C-face.
[0029] Patent document 1 discloses surface modification of aggregated hexagonal boron nitride with a silane coupling agent having a vinyl group. It is believed that the silane coupling agent chemically bonds to the boron nitride by dehydration condensation with the hydroxyl groups present on the surface of the boron nitride. However, the amount of hydroxyl groups present on the C-face of the scaly hexagonal boron nitride is small. Therefore, it cannot be considered that a sufficient amount of silane coupling agent can be adsorbed on the C-face of the boron nitride. That is, it is believed that according to the method of patent document 1, the hydroxyl-rich face other than the C-face is modified with a silane coupling agent. In this case, the effect of inhibiting the adsorption of water on the C-face is limited. In addition, the silyl group contained in the silane coupling agent is easily changed into a silanol group having a hydroxyl group by a hydrolysis reaction. Therefore, the silane coupling agent can be a direct cause of the deterioration of the dielectric loss tangent.
[0030] However, dopamine-containing proteins secreted from the byssus gland of blue mussels, a type of bivalve molluscs, are widely known as natural adhesives that exhibit stable adhesive force even in seawater. According to Non-Patent Document 1, dopamine adheres to the surfaces of various materials under alkaline conditions and undergoes oxidative polymerization to form a polydopamine film.
[0031] For example, non-patent document 2 discloses the C-face of boron nitride coated with polydopamine. However, water is easily adsorbed on the surface treated with a hydrophilic surface modifier such as polydopamine. Polydopamine itself also has a large amount of hydroxyl groups. Therefore, when polydopamine is used as a surface modifier for boron nitride, the dielectric loss tangent of boron nitride deteriorates.
[0032] Non-Patent Document 3 discloses that the C-face of a boron nitride nanosheet is surface-modified using a polystyrene moiety of a block copolymer of polystyrene and PMMA.
[0033] However, the thickness of the boron nitride nanosheet in the C-axis direction is only a few nm. The surface area of the boron nitride nanosheet per unit mass reaches tens to hundreds of times that of the usual flaky boron nitride. Therefore, when forming a boron nitride nanosheet, the area that can absorb water increases, and the deterioration of hygroscopicity and the dielectric loss tangent under high humidity are expected. Furthermore, the separation of boron nitride nanosheets not only requires complicated steps, but also has a low yield, and there are problems in the industrial utilization.
[0034] In addition, the results of the present inventors' research show that the surface of the flaky boron nitride that is not a nanosheet has not been fully modified with polystyrene. Boron nitride nanosheets have a structure that allows flaky boron nitride to be thinly peeled off along the C surface. The thickness of the boron nitride nanosheet in the C-axis direction is several nm, which is equivalent to a single atomic layer to several atomic layers. Therefore, compared with the flaky boron nitride with a thickness of several 10nm to several 100nm in the C-axis direction, the structure of the boron nitride nanosheet is thermodynamically unstable. This is believed to be the reason why organic molecules are easily adsorbed on the surface of the boron nitride nanosheet.
[0035] Therefore, all the conventional examples cannot reduce the hygroscopicity of hexagonal boron nitride under high humidity, nor can they reduce the dielectric loss tangent of boron nitride.
[0036] The present inventors have conducted intensive research on polymers that enable surface modification of hexagonal boron nitride. As a result, they have found that the above-mentioned problems can be solved by attaching a polymer that can achieve a specific solubility parameter (SP value) to the surface of boron nitride, thereby completing the present disclosure.
[0037] (Overview of one aspect of the present disclosure)
[0038] The boron nitride material according to the first embodiment of the present disclosure comprises: hexagonal boron nitride having a thickness of 5 nm or more in the C-axis direction, and a polymer attached to the hexagonal boron nitride, wherein the solubility parameter (SP value) of the boron nitride material measured by a methanol titration method is lower than 47.9 MPa 0.5 .
[0039] According to the present disclosure, the dielectric loss tangent of a boron nitride material under high humidity can be reduced.
[0040] In the second aspect of the present disclosure, for example, according to the boron nitride material involved in the first aspect, the polymer may be attached to the C-plane of the hexagonal boron nitride. By attaching the polymer to the C-plane of the hexagonal boron nitride, the surface modification effect can be fully obtained.
[0041] In the third embodiment of the present disclosure, for example, according to the boron nitride material involved in the first or second embodiment, the polymer may include a polyvinyl aromatic polymer, and the polyvinyl aromatic polymer may include a side chain containing a heteroaromatic ring. By having such a structure, the polymer can be strongly adsorbed on the surface of the boron nitride.
[0042] In a fourth embodiment of the present disclosure, for example, according to the boron nitride material involved in any one of the first to third embodiments, the polymer may include a repeating unit represented by formula (1). In formula (1), n represents a positive integer, X is represented by formula (2), and R in formula (2) is 1 To R 5 Any one of represents a direct bonding point with the main chain contained in the repeating unit, R 1 To R 5 The remaining four of the above-mentioned structures independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. By having such a structure, the polymer can be strongly attached to the surface of boron nitride.
[0043] [Chemical formula number 1]
[0044]
[0045] In a fifth embodiment of the present disclosure, for example, according to the boron nitride material involved in the fourth embodiment, in the formula (2), R 1 To R 5 The remaining four of R can be independently H atoms or hydrocarbon groups. From the viewpoint of improving the hydrophobicity of the polymer, R 1 To R 5 The remaining four are H atoms or hydrocarbon groups.
[0046] In a sixth aspect of the present disclosure, for example, according to the boron nitride material involved in the fourth aspect, in the formula (1), X can be represented by the formula (3). 11 To R 19 Any one of represents a direct bonding point with the main chain, R 11 To R 19 The remaining eight of the above-mentioned structures independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. By having such a structure, the polymer is strongly adsorbed on the surface of boron nitride.
[0047] [Chemical formula number 2]
[0048]
[0049] In a seventh embodiment of the present disclosure, for example, according to the boron nitride material involved in the sixth embodiment, in the formula (3), R11 To R 19 The remaining eight of R can be independently H atoms or hydrocarbon groups. From the viewpoint of improving the hydrophobicity of the polymer, R 11 To R 19 The remaining eight are H atoms or hydrocarbon groups.
[0050] In the eighth embodiment of the present disclosure, for example, according to the boron nitride material involved in the first embodiment, the polymer may include the following repeating units, wherein the repeating units include at least one selected from a carbazole skeleton and a fluorene skeleton. By including at least one selected from a carbazole skeleton and a fluorene skeleton in the repeating units of the polymer, the polymer can be strongly adsorbed on the surface of the boron nitride.
[0051] In a ninth aspect of the present disclosure, for example, in the boron nitride material according to the eighth aspect, the fluorene skeleton may include at least one substituent.
[0052] In the tenth aspect of the present disclosure, for example, in the boron nitride material according to the first aspect, the polymer may include a repeating unit containing a polyphenylene ether skeleton. When the repeating unit of the polymer includes the polyphenylene ether skeleton, the polymer may be strongly adsorbed on the surface of the boron nitride.
[0053] In the eleventh aspect of the present disclosure, for example, according to the boron nitride material involved in the tenth aspect, the polyphenylene ether skeleton may include at least one substituent.
[0054] The twelfth aspect of the present disclosure relates to a filler comprising the boron nitride material of any one of the first to eleventh aspects. According to the filler of the present disclosure, the heat resistance of the filler can be improved, and the generation of bubbles when the filler is heated can also be suppressed.
[0055] The resin composition according to the thirteenth aspect of the present disclosure includes the filler according to the twelfth aspect. According to the thirteenth aspect, a resin composition having a low dielectric loss tangent and excellent heat resistance can be provided.
[0056] A prepreg according to a fourteenth aspect of the present disclosure includes the resin composition according to the thirteenth aspect or a semi-cured product of the resin composition.
[0057] A film with resin according to a fifteenth aspect of the present disclosure comprises: a resin layer including the resin composition according to the thirteenth aspect or a semi-cured product of the resin composition; and a support film.
[0058] A metal foil with resin according to a sixteenth aspect of the present disclosure comprises: a resin layer including the resin composition according to the thirteenth aspect or a semi-cured product of the resin composition; and a metal foil.
[0059] A metal-clad laminate according to a seventeenth aspect of the present disclosure comprises an insulating layer including a cured product of the resin composition according to the thirteenth aspect or a cured product of the prepreg according to the fourteenth aspect, and a metal foil.
[0060] The wiring board according to the eighteenth aspect of the present disclosure comprises: an insulating layer formed of a cured product of the resin composition according to the thirteenth aspect or a cured product of the prepreg according to the fourteenth aspect; and wiring.
[0061] According to the fourteenth to eighteenth aspects, various application products suitable for high frequencies can be provided.
[0062] (Implementation Method 1)
[0063] Figure 1 This is a diagram showing a schematic configuration of a boron nitride material 10 in Embodiment 1. The boron nitride material 10 includes a boron nitride 1 and a polymer 2. The polymer 2 is attached to the boron nitride 1.
[0064] [Boron Nitride]
[0065] Boron nitride 1 is hexagonal boron nitride (h-BN). Hexagonal boron nitride can be synthesized relatively easily and has excellent properties such as thermal conductivity, electrical insulation, chemical stability, and heat resistance, and is therefore suitable for the boron nitride material 10 of the present disclosure.
[0066] The boron nitride 1 has a particle shape. The shape of the boron nitride 1 particle is not particularly limited as long as the C-plane to be modified is exposed on the surface. Since the C-plane has a large area, the boron nitride 1 particle is preferably scaly in shape.
[0067] The thickness of the boron nitride 1 in the C-axis direction is, for example, greater than 5 nm. By having a thickness of greater than 5 nm, the surface area per unit mass of the boron nitride 1 can be reduced. This is advantageous for reducing the amount of moisture adsorbed by the boron nitride 1 under high humidity and keeping the dielectric loss tangent of the boron nitride material 10 low. There is no particular upper limit on the thickness of the boron nitride 1 in the C-axis direction. The thickness of the boron nitride 1 in the C-axis direction may be less than 10 μm. The thickness of the boron nitride 1 in the C-axis direction may be greater than 10 nm and less than 10 μm.
[0068] The thickness of the boron nitride 1 in the C-axis direction can be measured using a scanning electron microscope image (SEM image) of the boron nitride 1. The widest surface of hexagonal boron nitride is the C-plane. Therefore, the thickness of the side surface of the boron nitride 1 in the SEM image can be regarded as the thickness in the C-axis direction.
[0069] There is no particular limitation on the average particle size of boron nitride 1. The average particle size of boron nitride 1 may be, for example, greater than 0.05 μm and less than 100 μm, or greater than 0.1 μm and less than 50 μm. In the present disclosure, the average particle size of boron nitride particles refers to the median diameter. The so-called median diameter refers to the particle size (d50) when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, using a laser diffraction measuring device.
[0070] [polymer]
[0071] The polymer 2 is an organic compound that functions as a surface modifier of the boron nitride 1. The polymer 2 is attached to the C-face of the boron nitride 1. Since most of the surface area of the hexagonal boron nitride is the C-face, the surface modification effect can be fully obtained by attaching the polymer 2 to the C-face.
[0072] The polymer 2 can form a film on the C-face of the boron nitride 1. The polymer 2 can be attached to the entire C-face or only to a portion of the C-face. The polymer 2 can be attached to a surface other than the C-face. For improving hygroscopicity, modification of the C-face is effective, and when both the C-face and the surface other than the C-face are modified, hygroscopicity can also be improved.
[0073] The polymer 2 may be a polymer having an aromatic ring in the repeating unit. Since the C-face of hexagonal boron nitride is inactive, it is not easy to chemically modify the C-face. In this embodiment, the polymer 2 is physically adsorbed on the boron nitride 1. "Physical adsorption" means that adsorption is mainly performed by van der Waals forces.
[0074] The polymer 2 can be physically adsorbed on the C-face of the boron nitride 1 by utilizing the π-π interaction. The π-π interaction that acts in the aromatic ring is also known as a particularly strong interaction among the van der Waals forces. A sufficient amount of the polymer 2 can be adsorbed on the C-face of the boron nitride 1 by utilizing the van der Waals forces including the π-π interaction.
[0075] In this embodiment, the HSP (Hansen solubility parameter) distance between polymer 2 and water is 39.5 MPa. 0.5 Large. The HSP distance is calculated using the group contribution method (Hansen method). A sufficiently large HSP distance between polymer 2 and water means that polymer 2 has high hydrophobicity. By having high hydrophobicity in polymer 2, the hygroscopicity of boron nitride material 10 can be reduced. As a result, the dielectric loss tangent of boron nitride material 10 under high humidity can be reduced. There is no particular limit on the upper limit of the HSP distance between polymer 2 and water. The upper limit of the HSP distance is, for example, 54.8 MPa. 0.5 .
[0076] Generally, when a covalent bond is formed between the surface modifier and boron nitride by a chemical reaction such as dehydration condensation, a compound containing a highly reactive polar group is used as the surface modifier. Since a compound containing a polar group has high hydrophilicity, the HSP distance between the compound and water is likely to be 39.5 MPa. 0.5 Therefore, in the case of surface modification using a hydrophobic compound, surface modification by physical adsorption is preferred over formation of a covalent bond by a chemical reaction.
[0077] Whether the amount of polymer 2 attached to the boron nitride 1 is sufficient, that is, whether the surface modification is sufficient, can be determined by measuring the solubility parameter (SP value) of the boron nitride material 10 by methanol titration. 0.5 When the surface of the boron nitride material is hydrophilic, its SP value is 47.9MPa. 0.5 As the polymer 2 is sufficiently attached to the surface of the boron nitride 1, the surface of the boron nitride material changes to be hydrophobic, and its SP value becomes lower than 47.9 MPa. 0.5 . When the SP value is suppressed to less than 47.9MPa 0.5 In the case of high humidity, the boron nitride material 10 shows a low dielectric loss tangent. There is no particular limitation on the lower limit of the SP value of the boron nitride material 10. The lower limit of the SP value of the boron nitride material 10 is, for example, 34.1 MPa. 0.5 .
[0078] The polymer 2 may include a polyvinyl-based aromatic polymer, and the polyvinyl-based aromatic polymer may include a side chain containing a heteroaromatic ring. By having such a structure, the polymer 2 can be firmly attached to the surface of the boron nitride 1.
[0079] The polymer 2 may have a repeating unit represented by formula (1). In formula (1), n represents a positive integer. X is represented by formula (2). R in formula (2) 1 To R 5 Any one of them represents a direct bonding point to the main chain contained in the repeating unit represented by formula (1). 1 To R 5 The remaining four of "R" independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. 1 To R 5 The "other four" means a site where no bonding point with the main chain is formed. The main chain in formula (1) is an ethylene skeleton. By having such a structure, the polymer 2 can be firmly adsorbed on the surface of the boron nitride 1.
[0080] [Chemical formula number 3]
[0081]
[0082] R 1 To R 5 The remaining four may independently be a hydrogen atom, a halogen atom, a hydrocarbon group, a halogenated hydrocarbon group, a group containing an oxygen atom, a group containing a nitrogen atom, a group containing a sulfur atom, a group containing a silicon atom, a group containing a phosphorus atom, or a group containing a boron atom.
[0083] Examples of the halogen atom include F, Cl, Br and I.
[0084] Examples of the hydrocarbon group include an aliphatic saturated hydrocarbon group, an alicyclic hydrocarbon group, and an aliphatic unsaturated hydrocarbon group.
[0085] The so-called halogenated hydrocarbon group refers to a group in which at least one hydrogen atom contained in the hydrocarbon group is replaced by a halogen atom. The halogenated hydrocarbon group may be a group in which all hydrogen atoms contained in the hydrocarbon group are replaced by halogen atoms. Examples of the halogenated hydrocarbon group include halogenated alkyl groups and halogenated alkenyl groups.
[0086] The group containing an oxygen atom is, for example, a substituent having at least one selected from a hydroxyl group, a carboxyl group, an aldehyde group, an ether group, an acyl group, and an ester group.
[0087] The group containing a nitrogen atom is, for example, a substituent having at least one selected from an amino group, an imino group, a cyano group, an azido group, an amide group, a carbamate group, a nitro group, a cyanamide group, an isocyanate group, and an oxime group.
[0088] The group containing a sulfur atom is, for example, a substituent having at least one selected from a thiol group, a thioether group, a sulfinyl group, a sulfonyl group, a sulfinyl group, a sulfonic acid group, an acylthio group, a sulfenamide group, a sulfonamide group, a thioamide group, a thiocarbamate group and a thiocyanate group.
[0089] The group containing a silicon atom is, for example, a substituent having at least one selected from a silyl group and a siloxy group.
[0090] The group containing a phosphorus atom is, for example, a substituent having at least one selected from a phosphine group and a phosphono group.
[0091] The group containing a boron atom is, for example, a substituent having a boronic acid group. Examples of the substituent having a boronic acid group include a boronic acid group itself and a hydrocarbon group having a boronic acid group.
[0092] R 1 To R 5 The remaining four in may be independently H atoms or hydrocarbon groups. H atoms or hydrocarbon groups do not increase the polarity of polymer 2. Therefore, from the viewpoint of improving the hydrophobicity of polymer 2, it is preferred that R1 To R 5 The remaining four are H atoms or hydrocarbon groups.
[0093] Examples of the hydrocarbon group include an aliphatic saturated hydrocarbon group, an alicyclic hydrocarbon group, an aliphatic unsaturated hydrocarbon group, and the like. The aliphatic saturated hydrocarbon group may be an alkyl group. Examples of the aliphatic saturated hydrocarbon group include -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH(CH3)CH2CH3, -C(CH3)3, -CH2CH(CH3)2, -(CH2)3CH3, -(CH2)4CH3, -C(CH2CH3)(CH3)2, -CH2C(CH3)3, -(CH2)5CH3, -(CH2)6CH3, -(CH2)7CH3, -(CH2)8CH3, -(CH2)9CH3, -(CH2) 10 CH3, -(CH2) 11 CH3, -(CH2) 12 CH3, -(CH2) 13 CH3, -(CH2) 14 CH3, -(CH2) 15 CH3, -(CH2) 16 CH3, -(CH2) 17 CH3, -(CH2) 18 CH3, -(CH2) 19 Examples of alicyclic hydrocarbon groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and adamantyl. Examples of aliphatic unsaturated hydrocarbon groups include -CH=CH2, -C≡CH, -C≡CCH3, -C(CH3)=CH2, -CH=CHCH3, and -CH2CH=CH2.
[0094] The number of carbon atoms in the hydrocarbon group is not particularly limited, and may be, for example, 1 to 20, 1 to 10, or 1 to 5. The hydrocarbon group may be linear, branched, or cyclic.
[0095] In formula (1), X can be represented by formula (3). 11 To R 19 Any one of them represents a direct bonding point with the main chain contained in the repeating unit represented by formula (1). 11 To R 19 The remaining eight of "R" independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. 11 To R 19The "remaining eight" means a site where no bonding point with the main chain is formed. By having such a structure, the polymer 2 can be strongly adsorbed on the surface of the boron nitride 1.
[0096] [Chemical formula number 4]
[0097]
[0098] R 11 To R 19 The remaining eight of R can be independently hydrogen atoms, halogen atoms, hydrocarbon groups, halogenated hydrocarbon groups, groups containing oxygen atoms, groups containing nitrogen atoms, groups containing sulfur atoms, groups containing silicon atoms, groups containing phosphorus atoms, or groups containing boron atoms. 11 To R 19 For example, R 1 To R 5 In the example described above.
[0099] R 11 To R 19 The remaining eight of R can be independently H atoms or hydrocarbon groups. H atoms or hydrocarbon groups do not increase the polarity of polymer 2. Therefore, from the viewpoint of improving the hydrophobicity of polymer 2, it is preferred that R 11 To R 19 The remaining eight are H atoms or hydrocarbon groups.
[0100] Polymer 2 may be a polymer represented by formula (4). That is, polymer 2 may have a structure other than the repeating unit represented by formula (1). In formula (1), n represents a positive integer, and m represents an integer greater than 0. X is represented by formula (2) or formula (3). R 6 The polymer 2 contains at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I, and Br. With such a structure, the polymer 2 can be strongly adsorbed on the surface of the boron nitride 1.
[0101] [Chemical formula number 5]
[0102]
[0103] For R 6 For example, R 1 To R 5 In the example described above.
[0104] R 6 It can be an H atom or a hydrocarbon group. The H atom or the hydrocarbon group does not increase the polarity of the polymer 2. From the viewpoint of improving the hydrophobicity of the polymer 2, it is preferred that R 6 It is a H atom or a hydrocarbon group.
[0105] In formula (4), m can be zero.
[0106] In addition, polymer 2 may have a repeating unit containing at least one selected from a carbazole skeleton and a fluorene skeleton. In the case of having a carbazole skeleton and a fluorene skeleton, polymer 2 can exert a strong adhesion to the C-face of boron nitride 1. The carbazole skeleton and the fluorene skeleton may be included in the main chain of polymer 2, or in the side chain. The carbazole skeleton and the fluorene skeleton may each have at least one substituent. At least one substituent may be a group containing at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. As such a group, the groups described above for formula (1) can be listed.
[0107] Polymer 2 may have a repeating unit containing a polyphenylene ether skeleton. In the case of having a polyphenylene ether skeleton, polymer 2 can exert a strong adhesion to the C-face of boron nitride 1. The polyphenylene ether skeleton may be contained in the main chain of polymer 2 or in a side chain. The polyphenylene ether skeleton may each have at least one substituent. At least one substituent may be a group containing at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br. As such a group, the groups described above with respect to formula (1) can be listed.
[0108] By having a carbazole skeleton, a fluorene skeleton, or a polyphenylene ether skeleton, the polymer 2 can be strongly attached to the surface of the boron nitride 1 .
[0109] It should be noted that, in order to reduce the hygroscopicity of boron nitride material 10, the HSP distance between polymer 2 and water is large. When the content of polar groups such as hydroxyl, carboxyl, unsubstituted amino, thiol, sulfonic acid, silanol groups is small, the HSP distance between polymer 2 and water can be large. In addition, when the content of polar groups is small, the dielectric loss tangent of polymer 2 itself can also be suppressed. Therefore, polymer 2 also may not have these polar groups. In addition, polymer 2 preferably does not produce these polar groups by reactions such as hydrolysis when hygroscopic.
[0110] There is no particular limitation on the molecular weight of the polymer 2. The polymer 2 has, for example, a number average molecular weight Mn of 100 or more. There is no particular limitation on the upper limit of the number average molecular weight Mn of the polymer 2, and it is, for example, 500,000.
[0111] The thermal decomposition temperature and boiling point of the polymer 2 are, for example, above 200°C, and can be above 250°C. The boron nitride material 10 is used, for example, as a filler in an insulating layer of a wiring board. When the thermal decomposition temperature of the polymer 2 is sufficiently high, the thermal decomposition or evaporation of the polymer 2 can be suppressed in the solder reflow process when mounting electronic components on the wiring board. Thus, the generation of bubbles between the wiring board and the resin layer can be prevented. In addition, according to the present embodiment, since the amount of water adsorbed by the boron nitride material 10 is suppressed, the generation of bubbles caused by the evaporation of adsorbed water in the solder reflow process can also be suppressed.
[0112] The amount of polymer 2 attached to boron nitride 1 is not particularly limited. For example, the ratio of the mass of polymer 2 to the mass of boron nitride 1 is 10% or less. By appropriately adjusting the amount of polymer 2 attached, the amount of gas generated during the thermal decomposition of boron nitride material 10 can be suppressed. This is particularly meaningful when using boron nitride material 10 as a filler. As long as the surface of boron nitride 1 can be sufficiently modified, the lower limit of the ratio of the mass of polymer 2 to the mass of boron nitride 1 is not particularly limited. The lower limit of the ratio is, for example, 0.01%.
[0113] There is no particular limitation on the method of surface modification of the boron nitride 1 using the polymer 2. For example, the boron nitride material 10 is obtained by mixing a solution containing the polymer 2 with the boron nitride 1, filtering, washing, and drying the solid matter.
[0114] There is no particular limitation on the temperature when the surface of boron nitride 1 is modified by using polymer 2, as long as the temperature is lower than the boiling point of the solvent. The surface modification can be performed at room temperature (20°C ± 15°C). There is no particular limitation on the type of solvent, as long as the polymer 2 can be dissolved. There is no particular limitation on the amount of polymer 2 used. The ratio of the mass of polymer 2 to the mass of boron nitride 1 can be greater than 0.01% and less than 10%, or can be greater than 0.75% and less than 5%.
[0115] [Boron nitride material]
[0116] Boron nitride material 10 has a structure that is favorable for reducing the dielectric loss tangent under high humidity. For example, the ratio of the dielectric loss tangent of boron nitride material 10 at 1 GHz in an atmosphere with a humidity of 90% to the dielectric loss tangent of boron nitride 1 at 1 GHz is less than 1. Therefore, boron nitride material 10 is suitable for applications requiring a low dielectric loss tangent, such as fillers for wiring boards. The lower limit of the ratio of the dielectric loss tangent of boron nitride material 10 to the dielectric loss tangent of boron nitride 1 is not particularly limited. The lower limit of the ratio is, for example, 0.001. It should be noted that in this specification, "humidity" refers to relative humidity.
[0117] The boron nitride material 10 has a structure that is advantageous for reducing the amount of moisture adsorption. For example, the ratio of the amount of moisture adsorbed by the boron nitride material 10 in an atmosphere with a humidity of 90% to the amount of moisture adsorbed by the boron nitride 1 in an atmosphere with a humidity of 90% is less than 1. By reducing the amount of moisture adsorption, the dielectric loss tangent can be reduced, and the generation of bubbles in the solder reflow process can also be suppressed. The lower limit of the ratio of the amount of moisture adsorbed by the boron nitride material 10 to the amount of moisture adsorbed by the boron nitride 1 is not particularly limited. The lower limit of the ratio is, for example, 0.01.
[0118] (Implementation Method 2)
[0119] The heat dissipation gap filler according to the present embodiment includes the boron nitride material 10 according to the first embodiment.
[0120] In the present disclosure, the so-called heat dissipation gap filler is a filler used to fill air pockets or gaps by applying to electronic components such as substrate materials to dissipate heat from electronic components. The heat dissipation gap filler is a curing heat dissipation paste that solidifies from a paste to a sheet. According to the heat dissipation gap filler involved in this embodiment, the heat resistance of the filler can be improved. It can also suppress the generation of bubbles during heating.
[0121] The heat dissipation gap filler according to the present embodiment can be produced by kneading, for example, the boron nitride material 10 according to the first embodiment and an epoxy resin or a silicone resin, or a non-silicone acrylic resin or a ceramic resin.
[0122] (Implementation 3)
[0123] The heat dissipating grease filler according to the present embodiment includes the boron nitride material 10 according to the first embodiment.
[0124] In the present disclosure, the heat dissipation grease filler is a filler used for heat dissipation grease. Heat dissipation grease is a non-curing heat dissipation paste used to fill air pockets and gaps by applying it to electronic components such as substrate materials, thereby dissipating heat from electronic components. According to the heat dissipation grease filler involved in this embodiment, the heat resistance of the filler can be improved. It is also possible to suppress the generation of bubbles during heating.
[0125] The heat dissipating grease filler according to the present embodiment can be produced by kneading the boron nitride material 10 according to the first embodiment, for example, with an epoxy resin or a silicone resin, or a non-silicone acrylic resin or a ceramic resin.
[0126] (Implementation 4)
[0127] Figure 3 It is a figure which shows the schematic structure of the resin composition 20 in Embodiment 4. The resin composition 20 contains the filler 22 and the curable resin 24, for example.
[0128] The filler 22 includes the boron nitride material 10 described in Embodiment 1. According to this embodiment, a resin composition 20 having a low dielectric loss tangent and excellent heat resistance can be provided. As the filler 22, only the boron nitride material 10 may be used, or other filler materials such as silica particles may be used together with the boron nitride material 10.
[0129] Examples of the curable resin 24 include epoxy resins, cyanate compounds, maleimide compounds, phenolic resins, acrylic resins, polyamide resins, polyamideimide resins, thermosetting polyimide resins, and polyphenylene ether resins. As the curable resin 24, one or a combination of two or more selected from these can be used.
[0130] The resin composition 20 may contain other components. Examples of other components include curing agents, flame retardants, ultraviolet absorbers, antioxidants, reaction initiators, silane coupling agents, fluorescent whitening agents, photosensitizers, dyes, pigments, tackifiers, lubricants, defoamers, dispersants, leveling agents, glossing agents, antistatic agents, polymerization inhibitors, and organic solvents. As required, one or a combination of two or more selected from these can be used in the resin composition 20.
[0131] (Implementation 5)
[0132] The prepreg according to the fifth embodiment comprises Figure 3 The resin composition 20 or its semi-cured product and the fibrous substrate of the embodiment 4 shown. The fibrous substrate is present in the matrix of the resin composition 20 or the semi-cured product. The prepreg is a composite material of the resin composition 20 and the fibrous substrate. According to this embodiment, a prepreg suitable for a wiring board supporting high frequencies can be provided.
[0133] In the present embodiment, semi-cured material refers to a material in which the resin combination 20 is cured to a state midway to a degree that can be further cured. That is, the semi-cured material is a material in a state in which the resin combination 20 is semi-cured. For example, if the resin combination 20 is heated, its viscosity slowly decreases. If heating is continued, curing begins afterwards, and its viscosity slowly rises. In such a case, as a semi-cured state, the state of the resin combination 20 during the time from the moment when the viscosity rises to the moment when it is fully cured can be listed.
[0134] As the fibrous substrate, known materials used in various laminates for electrical insulating materials can be used. Examples of the fibrous substrate include glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, linter paper, and the like.
[0135] The resin composition 20 is impregnated into the fibrous base material by treatment such as impregnation or coating. The fibrous base material impregnated with the resin composition 20 is heated under predetermined heating conditions to obtain a prepreg in a pre-cured or semi-cured state according to the present embodiment.
[0136] (Implementation 6)
[0137] Figure 4 : is a cross-sectional view of a film 30 with resin in Embodiment 6. The film 30 with resin includes: a resin layer 32 including a resin composition 20 or a semi-cured product thereof, and a support film 34. According to this embodiment, a film 30 with resin suitable for an insulating layer can be provided. The resin layer 32 is supported by the support film 34. Figure 4 In the example of FIG. 3 , the support film 34 is disposed on the surface of the resin layer 32. However, another layer such as an adhesive layer may be provided between the resin layer 32 and the support film 34.
[0138] The resin layer 32 includes Figure 3 The resin composition 20 or its semi-cured product of the embodiment 4 shown may contain a fibrous substrate or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 32 is cured and changed into an insulating layer. An example of such an insulating layer is an insulating layer of a wiring board.
[0139] Any supporting film used for a film with a resin can be used without limitation as the supporting film 34. Examples of the supporting film 34 include resin films such as a polyester film and a polyethylene terephthalate film.
[0140] (Implementation 7)
[0141] Figure 5 : is a cross-sectional view of a metal foil 40 with resin in Embodiment 7. The metal foil 40 with resin includes: a resin layer 42 containing a resin composition 20 or a semi-cured product thereof, and a metal foil 44. The resin layer 42 is supported by the metal foil 44. According to this embodiment, a metal foil 40 with resin suitable for electronic circuit components such as wiring boards can be provided. Figure 5 In the example of FIG. 4 , the metal foil 44 is disposed on the surface of the resin layer 42. However, another layer such as an adhesive layer may be provided between the resin layer 42 and the metal foil 44.
[0142] The resin layer 42 includes Figure 3 The resin composition or semi-cured product of the embodiment 4 shown may contain a fibrous substrate or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 42 is cured and changed into an insulating layer. An example of such an insulating layer is an insulating layer of a wiring board.
[0143] As the metal foil 44, metal foil used for a resin-attached metal foil and a metal-clad laminate can be used without limitation. Examples of the metal foil include copper foil and aluminum foil.
[0144] (Implementation 8)
[0145] Figure 6 : is a cross-sectional view of a metal-clad laminate 50 in Embodiment 8. The metal-clad laminate 50 includes an insulating layer 52 and at least one metal foil 54. According to this embodiment, a metal-clad laminate 50 suitable for a wiring board can be provided. The insulating layer 52 includes Figure 3 The cured product of the resin composition 20 of the fourth embodiment or the cured product of the prepreg of the fifth embodiment is shown. The metal foil 54 is arranged on the surface of the insulating layer 52. In this embodiment, the metal foil 54 is arranged on the front and back surfaces of the insulating layer 52, respectively.
[0146] The metal-clad laminate 50 is typically manufactured using the prepreg of Embodiment 5. For example, 1 to 20 prepregs are stacked to form a laminate. A metal foil is arranged on one or both sides of the prepreg laminate, and heating and pressurizing are performed to obtain the metal-clad laminate 50. Examples of the metal foil 54 include copper foil, aluminum foil, and the like.
[0147] The molding conditions for producing the metal-clad laminate 50 can be applied to the molding conditions for producing, for example, an electrically insulating laminate or a multilayer board.
[0148] (Implementation method 9)
[0149] Figure 7 : is a cross-sectional view of a wiring board 60 in Embodiment 9. The wiring board 60 includes an insulating layer 62 and wirings 64. According to this embodiment, a wiring board 60 suitable for high frequencies can be provided. The insulating layer 62 includes Figure 3 The cured product of the resin composition 20 of the fourth embodiment or the cured product of the prepreg of the fifth embodiment shown in . The wiring 64 is supported by the insulating layer 62. Specifically, the wiring 64 is arranged on the insulating layer 62. The wiring 64 can be formed by partially removing the metal foil.
[0150] By using etching and other methods Figure 6 The metal foil 54 on the surface of the metal-clad laminate 50 shown is patterned (layout), thereby obtaining a wiring board 60 in which wiring 64 forming a circuit is provided on the surface of the insulating layer 62. That is, the wiring board 60 is obtained by partially removing the metal foil 54 on the surface of the metal-clad laminate 50 in a manner to form a circuit.
[0151] A new laminate can be formed by laminating the prepreg of Embodiment 5 on at least one surface of wiring board 60 and heating and pressing the laminate. When the metal foil on the surface of the obtained laminate is patterned to form wiring, a multilayer wiring board is obtained.
[0152] Example
[0153] Hereinafter, the present disclosure will be described in detail using examples and comparative examples. It should be noted that the present disclosure is not limited to the following examples.
[0154] Hereinafter, as boron nitride, scaly hexagonal boron nitride (manufactured by Denka Corporation, GP grade) was used.
[0155] [Example 1]
[0156] 15 mg of poly(9-vinylcarbazole) represented by formula (5) (manufactured by Aldrich, number average molecular weight Mn25000 to 50000) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred at 100°C overnight. The boron nitride was separated by suction filtration, washed with toluene, and vacuum dried at room temperature. Thus, about 200 mg of the powder of the boron nitride material of Example 1 was obtained.
[0157] [Chemical formula number 6]
[0158]
[0159] [Example 2]
[0160] 15 mg of poly(N-ethyl-2-vinylcarbazole) (manufactured by Aldrich) represented by formula (6) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred at 100°C overnight. The boron nitride was isolated by suction filtration, washed with toluene, and vacuum dried at room temperature. Thus, about 200 mg of powder of the boron nitride material of Example 2 was obtained.
[0161] [Chemical formula number 7]
[0162]
[0163] [Example 3]
[0164] 15 mg of poly (9,9-di-n-dodecylfluorene-2,7-diyl) (manufactured by Luminescence Technology, LT-A1016) represented by formula (7) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred at 100°C overnight. The boron nitride was separated by suction filtration, washed with toluene, and dried in vacuo at room temperature. Thus, about 200 mg of the powder of the boron nitride material of Example 3 was obtained.
[0165] [Chemical formula number 8]
[0166]
[0167] [Example 4]
[0168] 15 mg of PFOTBT (poly[2,7-(9,9-dioctyl-fluorene)-alternating copolymer-4,7-bis(thiophene-2-yl)benzo-2,1,3-thiadiazole]) (manufactured by Luminescence Technology, LT-S9419) represented by formula (8) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred at 100°C overnight. The boron nitride was separated by suction filtration, washed with toluene, and vacuum dried at room temperature. Thus, about 200 mg of powder of the boron nitride material of Example 4 was obtained.
[0169] [Chemical formula number 9]
[0170]
[0171] [Example 5]
[0172] 15 mg of polyphenylene ether (manufactured by SABIC Japan Co., Ltd.) represented by formula (9) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred overnight at 100°C. The boron nitride was isolated by suction filtration, washed with toluene, and vacuum dried at room temperature. Thus, about 200 mg of the powder of the boron nitride material of Example 5 was obtained.
[0173] [Chemical formula number 10]
[0174]
[0175] [Comparative Example 1]
[0176] Hexagonal boron nitride (manufactured by Denka Corporation, GP grade) was used as the boron nitride of Comparative Example 1 as it was.
[0177] [Comparative Example 2]
[0178] 15 mg of poly(4-vinylpyridine) represented by formula (10) (manufactured by Aldrich, weight average molecular weight Mw less than 60,000) was dissolved in 1 mL of chloroform to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred at 50°C overnight. The boron nitride was isolated by suction filtration, washed with chloroform, and vacuum dried at room temperature. Thus, about 200 mg of powder of the boron nitride material of Comparative Example 2 was obtained.
[0179] [Chemical formula number 11]
[0180]
[0181] [Comparative Example 3]
[0182] Boron nitride was added to a dopamine solution (23 mg / mL) whose pH was adjusted to 8.5 with tris-HCl. The solution temperature was set to 80°C and stirred with a magnetic stirrer for 24 hours to allow the polymerization reaction of dopamine to proceed and form polydopamine. After the reaction, the boron nitride was filtered, washed with water, and dried. Thus, a powder of the boron nitride material of Comparative Example 3 was obtained.
[0183] [Comparative Example 4]
[0184] 15 mg of polystyrene (manufactured by Aldrich, weight average molecular weight Mw35000) was dissolved in 1 mL of toluene to obtain a solution. 200 mg of boron nitride was suspended in the solution and stirred overnight at 100°C. Boron nitride was isolated by suction filtration, washed with toluene, and vacuum dried at room temperature. Thus, about 200 mg of powder of the boron nitride material of Comparative Example 4 was obtained.
[0185] <Calculation of HSP distance>
[0186] The HSP distance between the polymers used in Examples and Comparative Examples and water was calculated by the following method.
[0187] The dispersion term δ of the HSP value is calculated from the molecular structure of the polymer using the group contribution method (Hansen method). d , polar term δ p and the hydrogen bond term δ h By substituting these values into the mathematical formula (A1), the HSP distance (MPa) between the polymer and water is calculated. 0.5 ). As the dispersion term of HSP value of water, δ d , polar term δ p and the hydrogen bond term δ h , using 15.5MPa 0.5 、16.0MPa 0.5 and 42.3MPa 0.5The results are shown in Table 1.
[0188] HSP distance = [4(δ d -15.5) 2 +(δ p -16.0) 2 +(δ h -42.3) 2 ] 1 / 2 (A1)
[0189] It is known that the polydopamine used in Comparative Example 3 is a mixture having multiple molecular structures. In this specification, the HSP distance is calculated assuming that polydopamine has a single structure described in formula (11). Actual polydopamine is known to be a highly hydrophilic polymer. Even if polydopamine has a structure other than formula (11), its HSP distance will not be 39.5 MPa. 0.5 the following.
[0190] [Chemical formula number 12]
[0191]
[0192] The HSP distance is used as an index to indicate the solubility and dispersibility of solvents or organic molecules, such as the affinity. Therefore, the HSP distance between water and polymers can be used as a reference for quantitatively judging the degree of hydrophobicity or hydrophilicity of polymers. As can be understood from the measurement results described later in the Examples and Comparative Example 2, it can be judged that the HSP distance between water and polymers is greater than 39.5 MPa. 0.5 The polymer of the HSP distance has sufficient hydrophobicity for reducing the dielectric loss tangent of boron nitride when humidified.
[0193] <Measurement of dielectric loss tangent during humidification>
[0194] The boron nitride materials of the examples and comparative examples were humidified using the following method. The boron nitride material was placed in an open container. The container and the hygrometer were placed in a transparent plastic bag. The boron nitride material was humidified by allowing air at 25°C adjusted to a humidity of 90% to flow through the plastic bag while leaving it in this state for 15 hours. The humidity in the humidified plastic bag was confirmed to be maintained at 90% using a hygrometer. The humidified boron nitride material was taken out of the plastic bag.
[0195] After humidification, the dielectric loss tangent of the boron nitride material at a frequency of 1 GHz was measured. A cavity resonator (MS46122B manufactured by AET) was used in the measurement of the dielectric loss tangent. During the period from the end of humidification to the start of the measurement of the dielectric loss tangent, the boron nitride material was exposed to the outside air at room temperature (25°C). The measurement was performed 20 minutes after the end of humidification. The results are shown in Table 1. In Table 1, the dielectric loss tangent during humidification represents a value standardized by setting the dielectric loss tangent of Comparative Example 1 during humidification to 1.
[0196] This determination is implemented in order to judge whether the dielectric loss tangent during humidification is good. The dielectric loss tangent of unmodified boron nitride (Comparative Example 1) is set to 1 and the dielectric loss tangent of boron nitride material is standardized. That is, the ratio of the dielectric loss tangent of boron nitride material and the dielectric loss tangent of unmodified boron nitride is calculated. If the value calculated is less than 1, it can be judged that the dielectric loss tangent is good.
[0197] <Measurement of water adsorption amount>
[0198] The boron nitride materials of the embodiments and comparative examples were humidified by the method described above. The amount of moisture adsorbed by the humidified boron nitride material was determined by the Karl-Fischer method. A Karl-Fischer moisture meter (MKC-610 manufactured by Kyoto Electronics Industry Co., Ltd.) and a vaporizer (ADP-611 manufactured by Kyoto Electronics Industry Co., Ltd.) were used in the measurement. The vaporization temperature was 150°C. The moment when the drift value reached +0.1μg / second was set as the end point. Nitrogen (200mL / min) was used as a carrier gas. Two measurements were performed, and the average value of the two times was used as the result. During the period from the end of humidification to the start of the measurement, the boron nitride material was stored in a gas replacement dryer filled with air at a humidity of 90%, and the boron nitride material was not allowed to contact the outside air until the start of the measurement. The results are shown in Table 1. In Table 1, the amount of moisture adsorbed during humidification represents a value standardized by setting the amount of moisture adsorbed during humidification of Comparative Example 1 to 1.
[0199] This determination is implemented in order to judge the water adsorption of the boron nitride material during humidification. The water adsorption of the unmodified boron nitride (Comparative Example 1) during humidification is set to 1 and the water adsorption of the boron nitride material is standardized. That is, the ratio of the water adsorption of the boron nitride material to the water adsorption of the unmodified boron nitride is calculated. If the calculated value is less than 1, it can be judged that the water adsorption is good.
[0200] <Determination of SP value (methanol titration method)>
[0201] The SP values of the boron nitride materials of the embodiments and comparative examples were determined by the method shown below. 50 mL of ion exchange water was placed in a 200 mL beaker, and 50 mg of boron nitride material was floated on the water surface. Then, a dispersion was obtained by stirring with a magnetic stirrer at a rotation speed of 300 rpm for 3 minutes. The top of the burette to which methanol was added was placed in the dispersion, and methanol was dripped under stirring, and the amount of methanol added Y (mL) required until all the particles of the boron nitride material were settled in the liquid was measured. The SP value was calculated by substituting the measured amount of addition Y into the mathematical formula (A2). In this embodiment, 47.9 MPa was used as the SP value of water (literature value). 0.5 As the SP value (literature value) of methanol, 29.6 MPa was used. 0.5 The results are shown in Table 1.
[0202] SP value = (47.9 × 50 + 29.6 × Y) / (50 + Y) (A2)
[0203] This measurement is performed to determine whether the surface of the boron nitride material of the embodiment and the comparative example is sufficiently hydrophobic. If the calculated SP value is lower than the SP value of water, i.e., 47.9 MPa, 0.5 When the amount of polymer attached to boron nitride is insufficient, or when the polymer is hydrophilic, the surface hydrophobicity of the boron nitride material is insufficient, and the SP value becomes 47.9 MPa. 0.5 above.
[0204] <Measurement of weight loss at 500°C>
[0205] The weight reduction of the boron nitride materials of the embodiments and comparative examples when heated from room temperature to 500°C was measured. A thermal analyzer (TG / DTA7200 manufactured by Hitachi High-Technologies Corporation) was used in the measurement. Thermogravimetric measurement was performed under a nitrogen atmosphere. The weight reduction from room temperature to 500°C can be evaluated as the adsorption amount of the polymer. The results are shown in Table 1.
[0206] Table 1
[0207]
[0208] As shown in Table 1, in Examples 1 to 5, the HSP distance between the polymer and water is 39.5 MPa. 0.5 The SP values of the boron nitride materials of Examples 1 to 5 are lower than 47.9 MPa. 0.5, the surface of the particles of the boron nitride material has sufficient hydrophobicity. Thus, it can be judged that the surface modification of boron nitride is fully carried out using a polymer in Examples 1 to 5. The dielectric loss tangent (relative to the ratio of Comparative Example 1) of the boron nitride material of Examples 1 to 5 is less than 1. That is, Examples 1 to 5 show a dielectric loss tangent lower than hexagonal boron nitride under high humidity. The moisture adsorption of the boron nitride material of Examples 1 to 5 (relative to the ratio of Comparative Example 1) is less than 1, which is lower than the moisture adsorption of Comparative Examples 1 and 3.
[0209] Figure 2 The coordinate diagram shows the relationship between the HSP distance between the polymer and water and the dielectric loss tangent of the boron nitride material when humidified. The horizontal axis represents the HSP distance between the polymer and water used in Examples 1 to 5 and Comparative Example 2. The vertical axis represents the dielectric loss tangent of the boron nitride material when humidified in Examples 1 to 5 and Comparative Example 2. For a total of 6 points in Examples 1 to 5 and Comparative Example 2, a linear approximation was performed using the least squares method to obtain Figure 2 The approximate straight line is represented by y = -0.0565x + 3.2323, and the determination coefficient R 2 It is 0.7061.
[0210] The HSP distance when the dielectric loss tangent during humidification is 1 is calculated from the approximate straight line. The HSP distance when the dielectric loss tangent during humidification is 1 is 39.5 MPa 0.5 Therefore, it is considered that if the HSP distance between the water and the water is 39.5MPa 0.5 When the large polymer sufficiently modifies the surface of boron nitride, the dielectric loss tangent when wetted can be reduced compared to that before the surface modification.
[0211] The polymers used in the boron nitride materials of Comparative Examples 2 and 3 have a relative humidity of 38.7 MPa. 0.5 and 27.2MPa 0.5 Therefore, it is considered that in Comparative Examples 2 and 3, the dielectric loss tangent when humidified is greater than the dielectric loss tangent of hexagonal boron nitride (Comparative Example 1).
[0212] Comparative Example 2 shows a small amount of water adsorption, but shows a high dielectric loss tangent. As the reason for obtaining such a result, it is speculated that the main reason is the deviation between the moisture content when measured by the Karl-Fischer method and the moisture content when the dielectric loss tangent is measured. The dielectric loss tangent is measured after the boron nitride material is transferred from an environment with a humidity of 90% to the atmosphere and 20 minutes later. That is, the "dielectric loss tangent when humidified" means the dielectric loss tangent in a state where a certain degree of water desorption has been performed. It is speculated that the desorption of water was fully carried out in Examples 1 to 5, but the desorption of water was not fully carried out in Comparative Example 2.
[0213] The measured value of Comparative Example 3 was not used for the calculation of the approximate straight line. This is because the polymer contained in the boron nitride material of Comparative Example 3 is polydopamine. Polydopamine does not have a single molecular structure, and the correct HSP distance cannot be calculated. In addition, the large amount of hydroxyl groups contained in its structure is the direct cause of the deterioration of the dielectric loss tangent. The data of Comparative Example 3 is judged to be unsuitable for discussing the influence of moisture absorption on the dielectric loss tangent, and thus it is excluded.
[0214] In Comparative Example 4, the HSP distance between the polymer (polystyrene) and water is sufficiently large. However, the SP value of the boron nitride material of Comparative Example 4 exceeds 47.9 MP. 0.5 That is, in Comparative Example 4, sufficient surface modification was not performed.
[0215] The reason why the polymers of Comparative Examples 2 to 4 failed to achieve sufficient surface modification is unclear, but it is presumed that the steric hindrance of the molecular chain and the low adsorption energy of the polymers on boron nitride have an effect.
[0216] In order to express the present disclosure, the present disclosure is appropriately and fully described above through the embodiments, but it should be recognized that those skilled in the art can easily change and / or improve the above embodiments. Therefore, as long as the changes or improvements implemented by those skilled in the art do not deviate from the level of the scope of rights of the claims recorded in the claims, the changes or improvements should be interpreted as being included in the scope of rights of the claims.
[0217] Industrial Applicability
[0218] The boron nitride material of the present disclosure shows a low dielectric loss tangent even under high humidity and is therefore suitable for wiring boards of electronic equipment used in large-capacity communications and the like.
[0219] Description of Reference Numerals
[0220] 1 Boron Nitride
[0221] 2 Polymer
[0222] 10 Boron Nitride Materials
[0223] 20. Resin composition
[0224] 22 Filling
[0225] 24 Curing resin
[0226] 30 Membrane with resin
[0227] 32 resin layer
[0228] 34 Support membrane
[0229] 40 Metal foil with resin
[0230] 42 Resin layer
[0231] 44 metal foil
[0232] 50 Metal-clad laminate
[0233] 52 Insulation layer
[0234] 54 metal foil
[0235] 60 Wiring Board
[0236] 62 Insulation layer
[0237] 64 Wiring.
Claims
1. A boron nitride material comprising: hexagonal boron nitride having a thickness of 5 nm or more in the c-axis direction, and a polymer attached to the hexagonal boron nitride, wherein the solubility parameter of the boron nitride material measured by methanol titration method is less than 47.9 MPa 0.5 .
2. The boron nitride material according to claim 1, wherein The polymer is attached to the C-face of the hexagonal boron nitride.
3. The boron nitride material according to claim 1, wherein The polymer comprises a polyvinyl-based aromatic polymer comprising a side chain containing a heteroaromatic ring.
4. The boron nitride material according to claim 1, wherein The polymer comprises a repeating unit represented by formula (1), wherein n represents a positive integer, and X is represented by formula (2), wherein R in formula (2) is 1 To R 5 Any one of represents a direct bonding point with the main chain contained in the repeating unit, R 1 To R 5 The remaining four of the above independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br, [Chemical formula number 1] 5. The boron nitride material according to claim 4, wherein: In the formula (2), R 1 To R 5 The remaining four are independently H atoms or hydrocarbon groups.
6. The boron nitride material according to claim 4, wherein: In the formula (1), X is represented by the formula (3), and R in the formula (3) is 11 To R 19 Any one of them represents a direct bonding point with the main chain, R 11 To R 19 The remaining eight of the above independently contain at least one atom selected from H, B, C, N, O, Si, F, P, S, Cl, I and Br, [Chemical formula number 2] 7. The boron nitride material according to claim 6, wherein: In the formula (3), R 11 To R 19 The remaining eight are independently H atoms or hydrocarbon groups.
8. The boron nitride material according to claim 1, wherein The polymer includes a repeating unit including at least one selected from a carbazole skeleton and a fluorene skeleton.
9. The boron nitride material according to claim 8, wherein: The fluorene skeleton includes at least one substituent.
10. The boron nitride material according to claim 1, wherein: The polymer comprises repeating units comprising a polyphenylene ether backbone.
11. The boron nitride material according to claim 10, wherein: The polyphenylene ether backbone comprises at least one substituent. 12 . A filler comprising the boron nitride material according to claim 1 . 13 . A resin composition comprising the filler according to claim 12 . 14 . A prepreg comprising the resin composition according to claim 13 or a semi-cured product of the resin composition. 15 . A film with a resin, comprising: a resin layer comprising the resin composition according to claim 13 or a semi-cured product of the resin composition; and a support film. 16 . A metal foil with resin, comprising: a resin layer comprising the resin composition according to claim 13 or a semi-cured product of the resin composition; and a metal foil. 17 . A metal-clad laminate comprising: an insulating layer comprising a cured product of the resin composition according to claim 13 or a cured product of the prepreg according to claim 14 ; and a metal foil. 18 . A wiring board comprising: an insulating layer comprising a cured product of the resin composition according to claim 13 or a cured product of the prepreg according to claim 14 ; and wiring.
Citation Information
Patent Citations
Plate box design and manufacture
JP1980030318A